(untitled) (Rudarsko-geološko-naftni zbornik, 2018)
The main aim of this paper is to develop a markovienne model for the evaluation of seismic hazard in the north-western part of Algeria. A region that accommodates from moderate to strong seismic activity (ML ≥ 2.5). This work is an attempt to conceive a stochastic model of the earthquake occurrences in order to assess the seismic hazard based on the use of a discrete time Markov chain with a finite state model. The presented model is applied on a complete data sample compris- ing most of the earthquakes that occurred in the Algerian northwestern area located between latitudes (34°N, 37°N) and longitudes (2°W, 3°E) since 1928 up to now (2018). The Markov chain is built over a homogeneous and completed cata- logue, then the transition probability matrix of the chain is used to simulate the occurrences of the earthquakes in the coming decades. The results are compared to a classic Poisson model.